IJAR 2019
DOI: 10.21474/ijar01/8878
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Effect of Polyethylene Glycol vs Lactulose in the Treatment of Overt Hepatic Encephalopathy.

Abstract: Inroduction : Hepatic encephalopathy is one of the most common cause of hospitalization for cirrhotic patients.. Lactulose has long been used as the standard therapy for the treatment of acute HE. This study evaluated the efficacy of PEG as compared with lactulose for the initial treatment of HE. Aims & Objective: (1) To compare efficacy of PEG 3350 electrolyte solution over lactulose in patients admitted for hepatic encephalopathy. (2) To determine whether treatment with PEG will reduce duration of hospital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…All the trials were designed in parallel groups and described as randomized. The generation of allocation sequences was adequately described; treatment allocation was fully hidden in 6 trials [10][11][12][14][15][16] ; single blinding was reported in 5 trials 10,11,[14][15][16] ; assessment of blinded outcomes was conducted in 2 trials. 10,14 The 6 trials were classified as high quality.…”
Section: Search Resultsmentioning
confidence: 99%
“…All the trials were designed in parallel groups and described as randomized. The generation of allocation sequences was adequately described; treatment allocation was fully hidden in 6 trials [10][11][12][14][15][16] ; single blinding was reported in 5 trials 10,11,[14][15][16] ; assessment of blinded outcomes was conducted in 2 trials. 10,14 The 6 trials were classified as high quality.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, only four RCTs met our inclusion criteria and were included in the qualitative and quantitative analysis. [12][13][14][15] The baseline characteristics of the included studies are depicted in table 1. Overall, there were a total of 229 patients (121 and 108 patients received PEG and lactulose, respectively).…”
Section: Literature Searchmentioning
confidence: 99%
“…Several randomised controlled trials (RCTs) evaluated the effectiveness of PEG versus lactulose in the treatment of HE; however, the results were inconsistent. [12][13][14][15] Herein, we conducted a systematic review and meta-analysis to assess the safety and clinical efficacy of PEG compared with the standard of care lactulose in patients with HE.…”
Section: Introductionmentioning
confidence: 99%
“…Two Indian randomized control trials reported significant improvement of HESA score in the PEG group when compared to lactulose. 86,87 Currently, two trials are under process to access the therapeutic use of PEG in HE. 88,89 Nitazoxanide Nitazoxanide (NTZ) is a broad-spectrum thiazolide antiparasitic agent which has action against many anaerobic bacteria, protozoa, and helminthic species.…”
Section: Polyethylene Glycolmentioning
confidence: 99%